Rural, Suburban, and Urban Differences in Factors That Impact Physician Adherence to Clinical Preventive Service Guidelines. Issue 1 (23rd May 2013) - Khoong, Elaine C.; Gibbert, Wesley S.; Garbutt, Jane M.; Sumner, Walton; Brownson, Ross C.
Abstract Purpose Rural‐urban disparities in provision of preventive services exist, but there is sparse research on how rural, suburban, or urban differences impact physician adherence to clinical preventive service guidelines. We aimed to identify factors that may cause differences in adherence to preventive service guidelines among rural, suburban, and urban primary care physicians. Methods This qualitative study involved in‐depth semistructured interviews with 29 purposively sampled primary care physicians (10 rural, 10 suburban, 9 urban) in Missouri. Physicians were asked to describe barriers and facilitators to clinical preventive service guideline adherence. Using techniques from grounded theory analysis, 2 coders first independently conducted content analysis then reconciled differences in coding to ensure agreement on intended meaning of transcripts. Findings Patient epidemiologic differences, distance to health care services, and care coordination were reported as prominent factors that produced differences in preventive service guideline adherence among rural, suburban, and urban physicians. Epidemiologic differences impacted all physicians, but rural physicians highlighted the importance of occupational risk factors in their patients. Greater distance to health care services reduced visit frequency and was a prominent barrier for rural physicians. Care coordination among health care providers was problematic for suburban and urban physicians. Patient resistance to medical care and inadequate access to resources and specialists were identified as barriers by some rural physicians. Conclusions The rural, suburban, or urban context impacts whether a physician will adhere to clinical preventive service guidelines. Efforts to increase guideline adherence should consider the barriers and facilitators unique to rural, suburban, or urban areas.